The Role of Indigenous Communities in Protecting The Environment After The Entry of Companies - Hattu, Vondaal Vidya; Tahamata, Lucia Charlota Octovina (Batulis Civil Law Review, 2024)
Introduction: The many cases of land disputes involving indigenous communities have created a bad image for this community.Purposes of the Research: The rights of indigenous peoples as well as the legal substance that forms the basis for the implementation of development in safeguarding the environment after the entry of the CompanyMethods of the Research: The method used is normative juridical with qualitative analysis.Results of the Research: The noble values in the lives of indigenous peoples seem to have disappeared due to a number of "conflicts" disputes. In fact, feuds and struggles are not the nature of indigenous peoples. This group is actually closely linked to environmental conservation efforts to ensure the continuity of life. This cultural identity requires a foothold which is known as customary territory. This area is very important because it is the living space and livelihood of the community. Customary territories include land, forests, seas and natural resources which are seen as a unity of economic, religious values and socio-cultural ties. The presence of the State can resolve problems that arise in society, especially environmental rights owned by indigenous peoples.